Influence of Solar Wind on Secondary Cosmic Rays and Atmospheric Electricity - Chum, Jaroslav; Kollárik, Marek; Kolmašová, Ivana; Langer, Ronald; Rusz, Jan; Saxonbergová, Dana; Strhárský, Igor (Frontiers in Earth Science, 2021)
A relationship between heliospheric magnetic field, atmospheric electric field, lightning activity and secondary cosmic rays measured on high mount of Lomnický Štít (2634 m a.s.l.), Slovakia, during declining phase of the solar cycle 24 is investigated with focus on variations related to solar rotation (about 27 days). The secondary cosmic rays are detected by neutron monitor and detector system SEVAN which distinguishes between different particles and energies. Using spectral analysis, we found distinct ~27–day periodicities in variations of Bx, By components of heliospheric magnetic field and in pressure corrected measurements of secondary cosmic rays. The 27–day variations of secondary cosmic rays on average advanced (lagged) the variations of Bx (By) components by about 40 (-140), respectively. Distinct 27–day periodicities were found both in the neutron monitor and SEVAN upper and middle detector measurements. A non–dominant periodicity of ~27 days was also found for lightning activity. A cross-spectral analysis between fluctuation of lightning activity and fluctuation of heliospheric magnetic field (HMF) showed that fluctuation of lightning activity was in phase and in antiphase with Bx and By components of HMF, respectively, which is in agreement with previous studies investigating influence of solar activity on lightning. On the other hand, the ~27–day periodicity was not significant in the atmospheric electric field measured in Slovakia and Czechia. Therefore, no substantial influence of Bx, By on atmospheric electric field was observed at these middle latitude stations.